2009
DOI: 10.3329/jhpn.v27i1.3319
|View full text |Cite
|
Sign up to set email alerts
|

Experience in Managing Severe Malnutrition in a Government Tertiary Treatment Facility in Bangladesh

Abstract: Children with severe acute malnutrition, defined as weight-for-height <70% of the reference median or bilateral pedal oedema or mid-arm circumference <110 mm having complications, were managed in the Nutrition Unit of the Chittagong Medical College Hospital (CMCH) following the guidelines of the World Health Organization, with support from Concern Worldwide Bangladesh and ICDDR,B. In total, 171 children aged less than five years (mean±SD age 23.5±15.3 months) were admitted during June 2005–May 2006. Of them, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
28
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 11 publications
7
28
7
Order By: Relevance
“…It is similar with studies done in Bangladesh tertiary Hospital [9] 10.8% and in Northcentral Nigeria 10.1% [13]. Though this outcome is below acceptable range, it is lower than another studies conducted in sub-Saharan Africa [11,14].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…It is similar with studies done in Bangladesh tertiary Hospital [9] 10.8% and in Northcentral Nigeria 10.1% [13]. Though this outcome is below acceptable range, it is lower than another studies conducted in sub-Saharan Africa [11,14].…”
Section: Discussionsupporting
confidence: 66%
“…The immediate causes of malnutrition and child death are mutually reinforcing conditions of inadequate dietary intake and infectious disease [3,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…1 To reduce the risk of death from severe acute malnutrition, specialized nutritional and medical intervention is required. Bacterial infection can complicate advanced cases of severe acute malnutrition, [2][3][4][5][6][7][8][9] and the risk of nosocomial infection in inpatient settings can be high. Therefore, in 1999, when all children with severe acute malnutrition were treated as inpatients, the World Health Organization (WHO) recommended routine use of broad-spectrum antibiotics for the management of severe acute malnutrition, irrespective of clinical indications.…”
mentioning
confidence: 99%
“…Likewise, in another studies by Savadogo et al, Patel et al and Iqbal et al, it was observed that mean weight gain was 10.18, 9.0 and 10.6 gm/kg/day respectively. [7][8][9] Iqbal et al also reported that during nutritional rehabilitation centre (NRC) stay 14.7% of the children demonstrated poor gain in weight (<5 gm/kg/day), 30.9% moderate (5-10 gm/kg/day), and the remaining 30.9% demonstrated good gain in weight (>10 gm/kg/day). 9 In our study, weight gain in 2nd week was more as compared to other weeks.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Iqbal et al also reported that during nutritional rehabilitation centre (NRC) stay 14.7% of the children demonstrated poor gain in weight (<5 gm/kg/day), 30.9% moderate (5-10 gm/kg/day), and the remaining 30.9% demonstrated good gain in weight (>10 gm/kg/day). 9 In our study, weight gain in 2nd week was more as compared to other weeks. There was significant more weight gain in 2nd week as compared to 3rd week (p<0.01).…”
Section: Discussionmentioning
confidence: 99%